Pemetaan Potensi Pengembangan Desa Agroindustri: Membangun Pusat Pertumbuhan Ekonomi Baru melalui Hilirisasi dari Desa di Jawa Tengah - Satrio, Roni Anom; Kurniawan, Bayu Dwi (Jurnal Dinamika Ekonomi Pembangunan, 2025)
This paper examines rural economic transformation in Central Java Province with a focus on village-based agroindustrial downstreaming. The study develops an Agroindustrial Village Development Potential Index (IPPDA) using factor analysis. The index captures five dimensions, including rural infrastructure, digitalization, village institutions, industrial activities, and access to energy. The results show that villages with high development potential are located in areas with strong infrastructure, institutional capacity, and economic activity. Villages with low potential are mostly found in highland regions and face constraints related to energy access, digital connectivity, and limited integration into local value chains. Spatial panel analysis shows that Village Original Income, Village-Owned Enterprises, and digitalization play a significant role in promoting agro sector development and industrialization. The analysis also identifies positive spatial spillover effects across districts. At the provincial level, agriculture plays a key role in supporting agroindustrial downstreaming. Central Java acts as an important hub within interregional agroindustrial value chains across Java, Bali, Nusa Tenggara, and eastern Sumatra. The findings highlight the importance of developing village-based agroindustrial clusters, strengthening local institutions, improving access to finance, and enhancing agro logistics connectivity.